dnl exposé

Views:
 
Category: Education
     
 

Presentation Description

No description available.

Comments

Presentation Transcript

Slide 2:

Al-Kashi

Slide 3:

Ulugh Beg observatory In Samarkand

Slide 4:

15/100

Slide 5:

P ythagoras T heorem A²=B²+C² If the triangle had a right angle, and you made a square on each of the three sides , then the biggest square had the exact same area as the other two squares put together .

Slide 6:

a²=b²+c²-2bc×cos(Â) b²=a²+c²-2ac×cos(B) c²=b²+a²-2ba×cos(C)

Slide 7:

How did he do? a²=b²+c²-2bc cos  D E P I K L M N

Slide 8:

How did he do? a²=b²+c²-2bc cos  h h E D P I K L M N

Slide 9:

How did he do? a²=b²+c²-2bc cos  E D P I K L M N

Slide 10:

How did he do? a²=b²+c²-2bc cos  E D P h I K L M N

Slide 11:

How did he do? a²=b²+c²-2bc cos  E D P I K L M N

Slide 12:

How did he do? a²=b²+c²-2bc cos  A3 A1 A2 A1+A2 =A3 A4 A5 AB²=BC²+AC²-(A4+A5)

Slide 13:

How did he do? a²=b²+c²-2bc cos  BC x E X = AC × cosα A5 A4

Slide 14:

A5 A5 = BC × AC × cosα A5 = BC × X X = AC × cosα

Slide 15:

How did he do? a²=b²+c²-2bc cos  y E Y = BC × cosα M AC A4 A5

Slide 16:

A4 A4 = AC × BC × cosα A4 = AC × Y Y = BC × cosα

Slide 17:

A4 = AC × BC × cosα A4 = AC × Y Y = CB × cosα A5 = BC × AC × cosα A5 = BC × X X = AC × cosα AB²=BC²+AC²-(A4+A5) AB²=BC²+AC²- AC × BC × cosα - BC × AC × cosα AB²=BC²+AC²- 2AC × BC × cosα

Slide 18:

AB²=BC²+AC²- 2AC × BC × cosα c²=a²+b²- 2ba × cosC

Slide 19:

With the Pythagoras Theorem A B C c b a H x b²=AH²+(a-x)² b²=c²-x²+a²+x²-2ax b²=c²+a²-2ax b²=c²+a²-2ac.cos(ABC)

Slide 20:

With the scalar product A B C c b a We know that : → → AB.AC=AB× AC×cos (BAC) → a²=BC² → → a²=(BA+AC)² → → a²=BA²+AC²+2BA.AC → → a²=c²+b²-2AB.AC ^ a²=b²+c²-2bc×cos(BAC)

Slide 21:

Verification of the Pythagoras Theorem b a c b²=c²+a²-2ac.cos(ABC) And Cos(ABC)=0 So b²=c²+a²

Slide 22:

Exercise A B C c b a I Demonstrate the formula: AI²=c²+a²/4- ac ×cos(B) a²=b²+c²-2bccos b²=a²+c²-2accosB c²=b²+a²-2bacosC

Slide 23:

Exercise A B C c b a I Demonstrate the formula: AI²=a²/4+ bc ×cos(A) a²=b²+c²-2bc×cos(Â) b²=a²+c²-2ac×cos(B) c²=b²+a²-2ba×cos(C) b²+c²=2AI²+a²/2

Slide 24:

Exercise A B C c b a I Express c in terms of a,b,cosB and cosA a²=b²+c²-2bc×cos(Â) b²=a²+c²-2ac×cos(B) c²=b²+a²-2ba×cos(C) b²+c²=2AI²+a²/2 AI²=c²+a²/4- ac ×cos(B) AI²=a²/4+ bc ×cos(A)

authorStream Live Help